2020
DOI: 10.15587/1729-4061.2020.219285
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for modelling delay propagation in railway networks using epidemiological SIR models

Abstract: A method has been developed to simulate propagation of train delays in branched railroad ranges using modified epidemiological SIR models. These models take into account the mutual influence of trains with different priorities in the flow. This makes it possible to study the heterogeneous dynamics in the propagation of delays among trains of different priorities. To consider the propagation of the primary delay in space and time, it is proposed to represent the topology of the railway network in the form of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Still, there are examples to be found. One example is Gurin et al (2020), which show that classic Susceptible-Infected-Recovered (SIR) modelling applied to railways help understanding primary delay evolution, making use of 'transit coefficients' to account for spreading of delays to adjacent stations [12]. Another example is the paper by Monechi et al (2018), which approaches the problem from a data perspective and infers 'laws' of railway delay propagation [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, there are examples to be found. One example is Gurin et al (2020), which show that classic Susceptible-Infected-Recovered (SIR) modelling applied to railways help understanding primary delay evolution, making use of 'transit coefficients' to account for spreading of delays to adjacent stations [12]. Another example is the paper by Monechi et al (2018), which approaches the problem from a data perspective and infers 'laws' of railway delay propagation [11].…”
Section: Discussionmentioning
confidence: 99%
“…An approach which is conceptually similar would be to shift perspective and define total delay on edges instead of stations, e.g. analogous to [12]. Such a model would automatically include the inherent directionality of trains.…”
Section: Potential Model Extensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi, Z. et al [7] used SIR model to simulate the propagation process of rail transit passenger congestion, found that the propagation rate affected the passenger congestion rate, and put forward policies to control passenger congestion from the two aspects of supply control and demand control. Gurin, D. et al [8] used the improved SIR model to simulate the train delay propagation process in the railway network, and studied and considered the delay propagation between trains with different priority levels. Zhao, Y. et al [9] established the SIR model of multi station fault delay propagation in urban rail transit operation, predicted the spatial impact range of station delay, and provided the basis for the safe operation of rail transit.…”
Section: Introductionmentioning
confidence: 99%